PREDICTIVE VALUE OF MOTOR ABILITIES ON THE RESULT IN CRITERIA VARIABLE SKI SHORT TURNS - Edin Mujanović,; Radivoje Krsmanović, (Sport Scientific And Practical Aspects, 2025)
Set of tests of motor abilities (as the predictor system) was used on a sample of 81 students of the Faculty for physical education and sport in Tuzla, for the purpose of determining predictive value of motor abilities on the results in criteria variable ski short turns. By means of a regression analysis the whole system of predictor variables is statistical significant, so based on these results, occasionally it can be reacted, because of the growth of the same (motor abilities) on the optimal level, for the easier mastering of the elements of Alpine skiing techniques.